Legal Protection Of Consumers On The Act Of Forced Retrieval Motorized Vehicle (Mk Decision Number 57/Puu-Xix/2021 Concerning Affirmation That Leasing Cannot Forcibly Take Vehicle If The Debtor Resists) - Gustiani, Hesti; Fajri, Ibrahim; Mustika, Desty Anggie (JURNAL MAHASISWA YUSTISI, 2024)
Based on the Constitutional Court's Decision, an alternative has been provided regarding the forced retrieval of vehicles carried out by leasing companies if the debtor objects and resists. Creditors or leasing companies cannot unilaterally execute fiduciary collateral or other forms of security such as vehicles or houses if the debtor objects or defaults. In the Constitutional Court's Decision Number 57/PUU-XIX/2021, it establishes legal provisions for law enforcement authorities to take action against Debt Collectors assigned by the Leasing Company who forcibly retrieve debtors' vehicles. Leasing companies cannot simply conduct forced retrievals from debtors. In Decision Number 57/PUU-XIX/2021, the Court addressed the execution mechanism for withdrawing the creditor's goods that are the object of fiduciary guarantees. The Constitutional Court stated that the Fiduciary Guarantee Certificate does not automatically confer executive authority. Regarding default between the debtor and creditor, based on legal efforts in a lawsuit to establish default, an application for execution must first be submitted to the district court to retrieve the fiduciary collateral. However, companies are allowed to execute without going through the court provided that the debtor's obligation to settle their debt is not used as a reason for engaging in forms of intimidation or terror.